Cost and Resource Use of Pemphigus and Pemphigoid Disorders Pre- and Post-Rituximab. Issue 3 (May 2015) - Heelan, Kara; Hassan, Shazia; Bannon, Grace; Knowles, Sandra; Walsh, Scott; Shear, Neil H.; Mittmann, Nicole
Background: Rituximab (RTX) is increasingly used for the treatment of pemphigus and pemphigoid disorders. The high cost of RTX frequently limits its use and access. Objective: To determine the health system resources and costs associated with RTX treatment of pemphigus and pemphigoid. Methods: Health system resources and costs attributed to a convenience sample of 89 patients with either pemphigus or pemphigoid were identified, quantified, and valued 6 months prior to and following RTX initiation between May 2006 and August 2012. Overall cohort costs and costs per patient were calculated (2013 Can$). Results: The overall cohort cost for 6 months pre-RTX was $3.8 million and for 6 months post-RTX was $2.6 million. The average cost per patient decreased from $42, 231 to $29, 423 (30.3% decrease). The main cost driver was intravenous immunoglobulin. Conclusions: Our findings suggest that RTX is effective in reducing health system resources and the costs associated with the treatment of pemphigus and pemphigoid.